Visualizations of Berea sandstone pores using neutron tomography. Issue 1 (November 2021) - Setiati, R; Sumirat, I; Sukaryo, S G; Adisoemarta, P S; Akbar, F; Marpaung, TS; Bharoto,
Abstract: Sandstone is a reservoir rock commonly found by oil and gas companies. Oil and gas usually trap inside the sandstone pores. A Destructive-Testing (DT) method or chemical solution method is usually used to measure the porosities of the sandstone sample. On the other hand, neutron computed tomography (NCT) can visualise and quantify all the porosities of the sandstone non-destructively. Neutron tomography is an imaging technique that employs neutron generated by a nuclear research reactor. The NCT produces cross-sectional images of the object that was used to visualise the Barea sandstone porosities distribution. The results show that each rock sample possesses connected and concentrated pores in the middle part of the rock with total porosity of ± 20%.